Homoleptic Co(II), Ni(II), Cu(II), Zn(II) and Hg(II) complexes of bis-(phenyl)-diisoindol-aza-methene. - Gresser, R; Hoyer, A; Hummert, M; Hartmann, H; Leo, K; Riede, M (Royal Society of Chemistry, 2011)
The synthesis of five homoleptic transition metal complexes of bis-(phenyl)-diisoindol-aza-methene is described together with the optical, electrochemical and thermal properties of these compounds. Additionally, crystal structures for the Co and the Zn complex are reported.